A PENGARUH PENERAPAN PROGRAM KESELAMATAN DAN KESEHATAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT.NUBUWA SALTIKA KOTA PALOPO - Anggun thia fianti; Haedar; Sari Ratna Dewi (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
This study aims to determine the effect occupational safety and health on the work productivity of employees of PT. Nubuwa Saltika Palopo. This research method uses the observation method by providing a list of statements about work safety (X1), occupational health (X2), work productivity (Y). Based on the results obtained in this study, it can be concluded that there is a significant simultaneous effect on employee productivity with Sig. F is 0,958%. smaller than the specified significant value that is equal to 0,05. While partially the work safety variable does not have a significant effect on employee work productivity indicated by the results of the regression analysis can be obtained Sig 0,776 with alpha 0,05. Where as the occupational health variable partially has a significant effect on employee work productivity with Sig 0,960 with alpha 0,05. Keywords : Safety, Health and Work Productivity of Employees